(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The current research aims to know the actual reality of the dimensions of health service quality provided by Bakhshin Hospital in Sulaymaniyah Governorate and to indicate the relative importance of the six Aims set by the American Institute of Medicine (IOM) represented by (Safety, Effectiveness, Efficiency, Timeliness, Patient-centered, Equity). To achieve this, the descriptive approach was used to collect and analyze data using the (SPSS 26) program, by choosing an intentional sample consisting of the staff (medical - health - administrative - technical). The questionnaire was the main tool for the research. The researchers reached a set of conclusions, the most important of which is the availability of quality health service from the perspective of the American Institute of Medicine at a good rate which reflects the awareness of the respondents of the research variables. Based on the conclusions, a set of proposals was developed, the most important of which are: providing a safe environment for employees and patients, enhancing patient safety, avoiding medical errors, and providing more safe services.